"It was the bruise of the war": The Effects of Injury and Trauma on the Construction of Masculinity in Hemingway and Lawrence - Bevilacqua, Thomas (Wake Forest University, 2010)
Ernest Hemingway and D.H. Lawrence were two authors best known, perhaps even infamous, for their portrayals of gender and particularly masculinity, which has led to the levying of criticisms and challenges by countless feminist critics. But rather than each author writing and reflecting a universal construction of masculinity, what emerges by considering the seminal post-World War I texts of these two authors is that they both possessed unique and nuanced constructions of masculinity that would often emerge in the wake of a physical injury or a psychological trauma. For Lawrence, masculinity was attained when a man embraced his impulse or inner essence, what scholar Peter Balbert outlines as the “phallic imagination,” while turning away from the control and mastery of the will. This choice that Lawrence’s men would make was often prompted by a physical or psychological wounding. By contrast, a physical injury or psychological trauma initiated Hemingway’s men and forced them to learn the importance of maintaining control and mastery, as living up to this “code” of self-control was the only way the Hemingway male could overcome their injury and survive. Lawrence’s construction of masculinity stressed impulse and emotion and the rejection of the will’s control, while for Hemingway masculinity was exerted when the man exhibited control over his impulses. By understanding the unique nature of each author’s construction of masculinity, we can in turn better understand their views and characterization of World War I, as well as realizing the nuanced nature of masculinity and how its further consideration could enrich future readings of the works of these two authors.
Keywords: Literature; Hemingway; Lawrence; 20th Century